Phytoconstituents and In Vitro Free Radical Scavenging Potential of n-Hexane and Aqueous Fractions of Cucurbita maxima and Leptadenia hastata - Dahiru, Mubarak Muhammad; Danga, James; Oni, Abdulhasib Oluwatobi; Zoaka, Hesper Alex; Peter, Rejoice Daniel; Zira, Usanye; Christopher, Patience; Alkasim, Hauwa Yahaya; Zainab, Muhammad (Sciences of Pharmacy, 2024)
The present study explored the phytoconstituents and radical scavenging activity of the respective n-hexane and aqueous fractions of Cucurbita maxima (CMHF and CMAF) and Leptadenia hastata (LHHF and LHAF) for potential application in oxidative stress-related ailments. The phytoconstituents were qualitatively determined and characterized using Fourier-transform Infrared (FTIR), while the antioxidant activity was determined in vitro. Alkaloids were present in only the aqueous fractions of C. maxima and L. hastata, while saponins, steroids, and flavonoids were detected in all the fractions. The FTIR revealed the presence of functional groups, including alcohols, sulfonates, alkenes, alkanes, amines, and aromatics in both plant fractions. The LHHF (35.53 ±2.11 ascorbic acid (AA) equivalent µg/mL) exhibited a significantly (p<0.05) higher total reducing power (TRP) than all the other fractions. The CMHF (69.11 ±2.56 AAE µg/mL) demonstrated a significantly (p<0.05) higher total antioxidant capacity (TAC) than all the other fractions. For the ferric thiocyanate (FTC) assay, the highest inhibition was exhibited by LHHF (79.78 ± 3.24%), significantly (p<0.05) higher than AA (26.46 ± 2.12%), CMHF (69.77 ± 3.16%), and CMAF (43.80 ± 2.12%). In the thiobarbituric acid assay, the lowest MDA concentration was exhibited by the CMHF (0.07 ±0.01 nmol/mL), significantly (p<0.05) lower than all the other fractions and ascorbic acid. Conclusively, the n-hexane fraction of both plants presents potential sources of novel antioxidant compounds with significant free radical scavenging and anti-lipid peroxidation activities, applicable in ailments linked to oxidative stress.